Morpho-Physiological Response of Sweet Corn (Zea mays L. Var saccharata Sturt) Bonanza F1 Variety to Drought Stress and Potassium Fertilizer Application - Datik Lestari; Akbar Maulana Firmansyah; Rizal Perlambang CNAWP; Mira Andriani; Theo Mahiseta Syahniar; Putri Rahayu Ratri (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
Sweet corn (Zea mays L. Var saccharata Sturt) has a high demand in Indonesia, but its productivity is threatened by drought; therefore, it is necessary to analyze its growth under drought stress conditions. This study aims to observe the morphological and physiological responses of sweet corn plants to drought stress and potassium administration. The research was conducted over a three-month period at the experimental garden of the Faculty of Agriculture, University of Riau. A Factorial Completely Randomized Design (RA LF) was used with two factors: drought stress and potassium fertilization. The study consisted of three levels of potassium fertilization, with three replications, resulting in a total of 18 experimental units. The first factor: A1 = everyday; A2 = drought stress. The second factor: K 1 = 2.3 g K 2 O plant -1; K 2 = 2.8 g K 2 O plant -1; K 3 = 180 kg K 2 O ha -1. Analysis of Variance was continued with the Honestly Significant Difference (HSD) test at 5% level. The observed parameters consisted of physiological and morphological factors in sweet corn plants. The study found that drought stress negatively impacted the physiological parameters of sweet corn, including reduced plant water content and increased proline levels. Additionally, drought stress decreased key morphological traits, including plant height, root condition, cob husk weight, cob husk length, and cob husk diameter. However, the application of potassium fertilizer, particularly at a dose of 3.4 g K₂O plant-1, significantly improved the length of the cob husk. Overall, increasing potassium application under drought stress conditions tended to enhance both morphological and physiological parameters of sweet corn.